An econometric model-based projection of Nigeria’s rice self-sufficiency - Abdul Hadi, Ahmad Hanis Izani; Abdulsalam, R. Y.; Shamsudin, Mad Nasir (Ferdowsi University of Mashhad, 2024)
Motivated by Nigeria’s persistent pursuit of rice self-sufficiency, this paper projects the country's future rice self-sufficiency levels. These projections could guide policy decisions in areas of the rice market that show potential for growth, aiding in the achievement of Nigeria's goal through improved planning strategies. Using time series data covering the period from 1980 to 2018, this study adopted an econometric technique to model Nigeria's rice market which was estimated using a dynamic Autoregressive Distributed Lag (ARDL) approach. The results revealed that paddy producer price elasticity was 0.206 and had no influence on paddy area harvested. On the other hand, the national policy of rice credit guarantee scheme variable displayed a positive relationship with paddy area harvested. Lagged yield and lagged area harvested had positive influences on yield and area harvested, respectively. This could mean that paddy producers were motivated by previous year’s yield levels and area harvested. The demand own-price elasticity of rice was -0.321 and its cross-price elasticity was 0.193, with wheat revealed to be a substitute. The obtained elasticities were then used to make a ten-year projection. Results suggested that by 2028, increasing rice production relative to dwindling imports will boost rice self-sufficiency level to 71%. However, the average yearly rice self-sufficiency level was 53%, requiring 3.85 million Mt of rice imports. The projections revealed that Nigeria will not achieve rice self-sufficiency by 2028 unless intensive yield enhancing policy-supporting efforts are pursued.